Islamic Ethics and Abortion In The Schools of Hanafiyah and Malikyah - Juhansar Andi Latief (Al-Ulum, 2010)
This study aims to discuss about abortion in Islamic ethical schools; Hanafiah and Malikiah Schools. Ethics and abortion are investigated, as well as their opinions and arguments about it. This is a library research conducted in order to find preconditions and arguments on abortion based on Islamic ethics. It sees and analyzes their different interpretation and understanding on abortion. This study then find that for Hanafiyans School, the iddah happens after 120 day or 4 months, while some of others say that it happens after 80 days there are some also state that it happens after 42 days. Otherwise, Malikiyans mention that it happens after 40 days. Abortion before iddah for most of Hanafiyah School is permitted. In contrast, most of Malikiyans totally forbid it even the fetus is still in the contraception period.